A protection scheme for distribution utility grid with wind energy penetration. (September 2021) - Mahela, Om Prakash; Bhati, Vikram Singh; Ahmad, Gulhasan; Khan, Baseem; Sanjeevikumar, P.; Garg, Akhil Ranjan; Mahla, Rajendra
Abstract: The impact of fault circumstances on distribution grid parameters in the presence of wind power generation is explored in this research. A protection algorithm (PA) is also proposed for detecting faulty events by using the proposed wind fault index, which is computed by analysing current signals using the Wigner distribution function and the Stockwell transform (ST). The sort of fault is determined by the number of faulty phases found. The zero sequence currents introduced to identify the ground's involvement in a fault event are analysed to calculate a wind ground fault index. Single phase to the ground, double phase to the ground, double phase, three-phases, and three phases to the ground faults are all investigated fault events. It has been determined that PA outperforms discrete Wavelet Transform and ST-based approaches in terms of fault estimation time and noise effect. The study was conducted on the IEEE-13 bus test feeder, which was connected to wind power plants (WPPs). Graphical abstract: